Hubungan Pola Asuh Orang Tua Dan Lama Durasi Penggunaan Gawai Terhadap Perkembangan Sosial Anak - Rifdah Faradillah; Dayan Hisni; Retno Widowati (Universitas Malahayati, 2022)
ABSTRACT Parenting styles and the use of gadgets in children greatly affect their development, one of which is social development. Many parents pay little attention to their children in regards to their use of gadgets. Many children spend their time in front of their gadgets instead of playing with their peers or interacting with other people. It certainly has a huge impact on their social development. This research sought to determine the relationship between parenting styles and the duration of gadget usage on children's social development. This descriptive quantitative research employed a cross-sectional approach. It involved 60 parents with preschool-age children (3-6 years) in RW 007 Kalibata Region - South Jakarta, selected through a total sampling technique. The research instruments used were a parenting style questionnaire, a questionnaire on the duration of gadget usage, and a questionnaire on children's social development. The obtained data were analyzed using univariate and bivariate analysis with a chi-square test. The research results, obtained from 60 respondents, revealed that many parents applied democratic parenting 26 (43%), with an average duration of gadget usage fell within normal of ≤ 1 hour 36 (60%), and the average children's social development was quite good 33 (55%). There is a relationship between parenting styles on children's social development and the duration of gadget usage on children's social development. Keyword: Parenting Parenting, Devices, Children's Social Development ABSTRAK Pola asuh orang tua dan penggunaan gawai pada anak sangat berpengaruh terhadap perkembangan anak, salah satunya pada perkembangan sosial. banyak orang tua yang jarang memperhatikan anak sehingga anak tidak terkontrol dalam penggunaan gawai. banyak anak yang menghabiskan waktunya didepan layar gawai dibandingkan bermain dengan teman sebayanya maupun berinteraksi dengan orang orang yang ada disekitarnya. hal itu tentunya sangat berdampak pada perkembangan sosial anak. Penelitian ini bertujuan untuk mengetahui hubungan pola asuh orang tua dan lama durasi penggunaan gawai terhadap perkembangan sosial anak. Desain penelitian ini adalah deskriptif kuantitatif dengan pendekatan cross sectional terhadap 60 orang tua yang memiliki anak usia prasekolah (3-6 tahun) di RW 007 Wilayah Kalibata - Jakarta Selatan dengan teknik sampel total sampling. Alat ukur yang digunakan adalah Kuesioner pola asuh orang tua, kuesioner lama durasi penggunaan gawai dan kuesioner perkembangan sosial anak. data yang didapatkan dianalisis menggunakan analisis univariat dan bivariat dengan uji chi square. Hasil yang didapatkan dari 60 responden paling banyak orang tua yang menerapkan pola asuh demokratis 26 (43,3%) dengan rata-rata durasi anak menggunakan gawai terbilang normal ≤1 jam 36 (60%) dan perkembangan sosial anak rata-rata cukup baik 33 (55%). Terdapat hubungan pola asuh orang tua terhadap perkembangan sosial anak dan lama durasi penggunaan gawai terhadap perkembangan sosial anak. Kata Kunci : Pola Asuh Orang Tua, Gawai, Perkembangan Sosial Anak.